Evaluation of Meniscal Load and Load Distribution in the Sound Canine Stifle at Different Angles of Flexion - Schmutterer, Johannes Maximilian; Augat, Peter; Greinwald, Markus; Meyer-Lindenberg, Andrea (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objectives The aim of the study was to investigate the contact mechanics and kinematic changes in the stifle in different standing angles.Study Design We performed a biomechanical ex vivo study using pairs of canine cadaver hindlimbs. Motion sensors were fixed to the tibia and the femur for kinematic data acquisition. Pressure mapping sensors were placed between the femur and both menisci. Thirty percent bodyweight was applied to the limbs with the stifle in 125, 135, or 145 degrees of extension.Results Stifle flexion angle influences femoromeniscal contact mechanics significantly. The load on both menisci was significantly higher for 125 and 135 degrees in comparison to 145 degrees. Additionally, the center of force was located significantly more caudal when comparing 125 to 145 degrees in the medial meniscus as well as in both menisci combined.Conclusion The angle of knee flexion significantly impacts the contact mechanics between the femur and the meniscus. As the knee flexes, the load on both menisci increases
Keywords: stifle joint; knee biomechanics; menisci; standing angle